Strategy to Improve Digital Literacy in Public Service Delivery in North Sumatra Province - Victor Lumbanraja; Februati Trimurti; Wiro Oktavius Ginting (Women, Education, and Social Welfare, 2026)
This study examines the planning, implementation, and service-quality implications of digital literacy strategies in North Sumatra’s public service delivery. Data were gathered from planning documents, including the Strategic Plan (Renstra), Work Plan (Renja), and the Government Agency Performance Accountability Report (LAKIP) of the Communication and Informatics Agency (Diskominfo), using a qualitative case study methodology. In-depth interviews were also conducted with key officials. The thematic analysis indicates a clear gap between policy planning, program implementation, and service outcomes. Although digital literacy has been incorporated into regional planning documents, its implementation is constrained by limited technical capacity among civil servants and the public, uneven program coverage, and the absence of legally binding cross-sectoral regulations. As a result, digital public service applications have not yet fully improved public engagement, service efficiency, and information transparency, particularly among vulnerable groups and rural communities. This study does not go into great detail about the role of national initiatives and private sector partners because it is restricted to provincial policy. However, in order to guarantee that digital literacy actually becomes a cornerstone of bureaucratic reform and inclusive public service delivery, the findings provide unique value in the form of a thorough understanding of the necessity of regional regulations, a critical competency-based literacy curriculum, behavior change based evaluation, and a multi-stakeholder collaborative ecosystem